Mutation of Host dnaJ Homolog Inhibits Brome Mosaic Virus Negative-Strand RNA Synthesis - Tomita, Yuriko (American Society for Microbiology, 2003)
The replication of positive-strand RNA viruses involves not only viral proteins but also multiple cellular proteins and intracellular membranes. In both plant cells and the yeast Saccharomyces cerevisiae, brome mosaic virus (BMV), a member of the alphavirus-like superfamily, replicates its RNA in endoplasmic reticulum (ER)-associated complexes containing viral 1a and 2a proteins. Prior to negative-strand RNA synthesis, 1a localizes to ER membranes and recruits both positive-strand BMV RNA templates and the polymerase-like 2a protein to ER membranes. Here, we show that BMV RNA replication in S. cerevisiae is markedly inhibited by a mutation in the host YDJ1 gene, which encodes a chaperone Ydj1p related to Escherichia coli DnaJ. In the ydj1 mutant, negative-strand RNA accumulation was inhibited even though 1a protein associated with membranes and the positive-strand RNA3 replication template and 2a protein were recruited to membranes as in wild-type cells. In addition, we found that in ydj1 mutant cells but not wild-type cells, a fraction of 2a protein accumulated in a membrane-free but insoluble, rapidly sedimenting form. These and other results show that Ydj1p is involved in forming BMV replication complexes active in negative-strand RNA synthesis and suggest that a chaperone system involving Ydj1p participates in 2a protein folding or assembly into the active replication complex.